The Challenge to Link Biology, Chemistry, and Physics: Results of a Longitudinal Study on Self-Rated Content Knowledge - Kevin Handtke; Susanne Bögeholz (MDPI AG, 2022)
Interdisciplinary science teaching in (lower) secondary education can lead to out-of-field teaching in countries with a discipline-specific teacher education. For example, the discipline-specific teacher education in Germany does not fit the current demands of interdisciplinary science teaching, especially in comprehensive schools. Self-rated content knowledge (srCK)-a specific part of academic self-concept-of (prospective) teachers is important in the context of motivational orientations and due to the reciprocal relation of academic self-concept and performance. Previous research did not focus on the long-term development of core idea-based srCK regarding secondary education. Thus, we surveyed 271 (prospective) teachers of biology, chemistry, and physics three times (2019-2021). In addition, we surveyed seven chemistry and physics pre-service teachers participating in a biology content knowledge (CK) course. Taking into account measurement invariance, we used structural equation modeling and latent change models. The srCK of biology, chemistry, and physics showed a high relative and absolute stability. We did not find any correlation between srCK of biology and chemistry. SrCK of chemistry and physics always showed a small positive correlation. SrCK of biology and physics always had a strong negative correlation. Supporting these results, studying physics had a negative effect on the srCK of biology, and studying chemistry had a positive effect on the srCK of physics. Additionally, studying the subject of the srCK in question always had a strong positive effect. Though srCK seems to be time-stable, a biology CK course for pre-service chemistry and physics teachers showed strong positive changes in their srCK of biology. Thus, training in an unstudied subject could help to cope with the undesired time-stability of srCK. In addition, the strong negative correlation between the srCK of biology and of physics needs to be addressed in teacher education.